Electricity access and social sustainability in Mozambique - Salite, Daniela; Cotton, Matthew; Kirshner, Joshua (Oxford Policy Management, 2020)
The demand for access to electricity in developing countries is rapidly increasing as intergovernmental organisations, national governments, and business leaders recognise the social and economic value of infrastructure investment. The institutions that govern energy investment and planning recognise a ‘trilemma’ of system development: low-carbon energy sources are needed to meet global climate change mitigation goals, while also meeting service reliability demands and energy security measures alongside maintaining service affordability, particularly for residents on the lowest incomes in rural, urban, and peri-urban communities. Integrating traditional, centralised grid networks based upon large-scale generation technologies (in the case of Mozambique, this includes hydropower from the Cahora Bassa Dam) with decentralised off-grid renewables such as solar projects in rural communities is a significant technical and governance challenge. Energy providers are tasked with a social mandate to deliver good quality electricity at an affordable price to consumers while widening access to underserved populations. Providing access to clean and reliable energy sources is embodied in Sustainable Development Goal 7 as one of the preconditions for socioeconomic development, poverty reduction, and human wellbeing (Pueyo and Maestre, 2019; UN Energy, 2005). International development practitioners and policy networks recognise the tangible benefits of electricity as a form of energy service provision. These tangible benefits include lighting and powering appliances at domestic, private, and institutional levels and increased telecommunications coverage, which collectively provide new personal and business development opportunities, healthcare and food safety benefits, and improved leisure and night-time education prospects (UN Energy, 2005). They also minimise the health risks and ecological impacts associated with black-carbon fuels such as charcoal, which diminish air quality within residential buildings (Anenberg, 2017) and lead to deforestation (Sedano et al., 2016). In order to enhance electricity sector performance, many sub-Saharan African countries have implemented significant governance reforms. It is necessary, however, to evaluate whether such reforms facilitate expanded social access to electricity, whether they improve service quality, public utility, and financial stability, and whether they lead to broader social and environmental sustainability goals. In this policy brief, we assess these dimensions related to the case of Mozambique, a country where major progress has been made to increase population-wide access to electricity from around 6% in 2004 (Chambal, 2010) to 32% in 2019 (EDM, 2020a). Though policy progress is significant, challenges remain, particularly in rural areas, where only around 6% of the population have electricity access (EDM, 2018a).
Keywords: G - Mozambique / Moçambique; L - english / inglês; climate change / mudanças climáticas; ⛔ No DOI found

LAND-at-Scale: Scaling Community Legal Literacy, Land Rights Certification and Climate Resilience in Mozambique - Centro Terra Viva-Estudos e Advocacia Ambiental (CTV); Firma, Terra (Rijksdienst voor Ondernemend Nederland (RVO), 2020)
The main objective of the Land at Scale Program is to increase community legal awareness and strengthen security of land tenure rights, creating capacity at local level to implement and leverage the progressive provisions of the Mozambican legal framework. The programme will contribute to community preparation to intervene in an informed manner in the land sector and will also contribute to the delimitation of community and individual land-use rights based on good faith occupation and customary rights, and their integration into the formal land system. To achieve these objectives, the proponents plan to conduct a large-scale campaign, across selected districts from all three regions of the national territory, with two main and interlinked interventions, namely: 1. Social Preparation & Legal Literacy (Component A), and 2. Community Land Rights Registration and Certification (Component B).
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; climate change / mudanças climáticas; governance / governação; land governance / gestão de terra

The Price of a Green Conscience - Brown, Jasmine; Ewald, Jonas; Fritz, Heiko (Linneaus University, 2020)
Scholars and civil society organizations have over the last decade referred to large-scale carbon sequestration TPPs as "carbon colonialism" (Carmody and Taylor, 2016) as well as a "development by dispossession" dressed in new clothing behind words such as climate change mitigation and development (Kröger, 2012). Concerns have been raised that the trade-offs from the implementation of industrial tree plantations (ITPs) may result in conflicting effects on countries' overall development (The Oakland Institute, 2019; Osborne, 2015; Nel & Hill, 2013). Moreover, NGO's and think tanks, such as FIAN (2012) and the Oakland Institute (2017, 2019), have released reports in which such tree planting projects are accused of displacing people and violating human rights (FIAN, 2012; The Oakland Institute, 2017, 2019; Carmody & Taylor, 2016). This thesis explores the impacts of carbon forestry projects, emphasizing the impacts of ITPs on local livelihoods and their subsequent effects on development. Three dimensions have been chosen to limit the scope of this thesis: (1) food security; (2) access to land; and (3) employment & income. The thesis is conducted using a qualitative desk study and secondary analysis of two multiple case studies of Uganda and Mozambique. The findings presented suggest carbon forestry projects may negatively affect all three dimensions, ultimately affecting communities' sustainable development. The author recommends further research to evaluate the complex effects of carbon forestry projects.
Keywords: *snowball; G - Mozambique / Moçambique; L - english / inglês; climate change / mudanças climáticas; poverty / pobreza